Fungos fitopatógenos associados às formigas cortadeiras (Formicidae: Tribo Attini) - Duarte, Ana Paula Miranda [UNESP] (2010)
The ants of genus Atta belong to the Attine tribe (order Hymenoptera, family Formicidae, subfamily Myrmicinae) and are commonly known as leaf-cutting ants for having the habit of cutting several vegetable species used as substrate for growing mutualistic fungus (Agaricales: Lepiotaceae). Recent studies showed that, in addition to that, other fungi may occur in the nests in a dorment state or participate in the functioning dynamic of this symbiosis. Researches related to surveys of fungus biodiversity in nests of different Atta species have found important phytopathogenic representatives. In Brazil, studies about integrated management of plagues, developed by Embrapa Meio Ambiente (Embrapa Environment), point out the need of higher investments in projects that involve the phytopathogenic transmission by insects in order to reduce costs to control them or minimize environmental impact. The purpose of this study was to broaden the knowledge about the ecology of these fungi, isolating and identifying species associated with Attine tribe ants, thus understanding the scope of pathogenic and phytopathogenic species spread by these ants. For that reason, gynes were collected from Atta laevigata and Atta capiguara anthills located at Unesp Botucatu (São Paulo, Brazil) campus. In order to isolate the fungus, the mineral oil floating technique was used. The identification of the isolated fungi was done based on microscopic and molecular characteristics using DNA ribosomal sequencing. The most highly abundant genera found so far were: Cladosporium, Exophiala, Penicillium, Acremonium, Phialophora and Teratosphaeria. Representatives of the genera Exophiala, Phialophora and Cladosporium may be human pathogens, whereas Teratosphaeria and Penicillium are related to diseases in Eucalyptus and citric fruits, respectively. The results show that these ants may host important fungal species besides the ones already... (Complete abstract click electronic access below)